A case of chronic granuloma related to wild‐type strain of rubella virus in an adult patient with ITK deficiency without primary immunosuppression and review of the literature - Caroline Bouvarel; Léa Luciani; Simon Sunder; Carine Motard; Sebastien Barbarot; Antoine Nougairède; Christine Zandotti; Xavier deLamballerie; Valérie Delargue; Cassandre Crémadès; Caroline‐Jade Clerc; Ingrid Kupfer‐Bessaguet (Wiley, 2024)
Abstract According to the review of the literature, rubella virus‐related granuloma is an entity first described in 2014 mainly affecting children with primary immune deficiencies infected with the rubella vaccine strain. The development of rubella virus‐associated granulomas seems to be related to a defect in cellular immunity and their severity varies from a simple cutaneous lesion to deep visceral involvement in some patients. Since then, this type of granuloma has been described in immunocompetent adults, including two cases involving a wild‐type strain of the virus (genotype 2). We report the case of a 70‐year‐old man had suffered from a granuloma of the leg for almost 40 years, in the absence of immunodeficiency. The assessment of the skin granuloma revealed a positive polymerase chain reaction for a wild‐type rubella virus genotype 1a. Genetic studies performed using whole exome sequencing suggest that the disease is due to a homozygous splice site mutation in the ITK gene.